Investigating Success Factors in Admission Test at Grade 8: A Survey Study of Cadet Colleges in Pakistan - Behlol, Malik Ghulam; Khan, Salma Nazar; Masood, Faiza; Jabeen, Farkhanda; Khurshid, Farhana (Pakistan Journal of Humanities and Social Sciences, 2023)
The fairness of the test for taking admission to prestigious institutions is a debatable issue across the globe. The majority of institutions apply a ‘traditional meritocratic approach’ to award admission on the basis of grades and admission tests. This paradigm does not fulfil the needs of marginalized, low socio-economic, poor-quality background students. The present study is descriptive and quantitative in nature, investigated the socioeconomic and academic factors of the students who were successful in securing admission to Cadet Colleges after passing the test and interview. We constructed two interview questionnaires for data collection from applicants. The sample of the study was comprised of 228 students for the session 2022 in selected institutions. The findings of the study highlight the low Socio-Economic Status as a strong factor in getting admission in prestigious education institutions. The results despairingly indicate that the admission test and stipulations at the interview to get enrolled in the institution do not equally address the learning competence of different streams thus putting a question about the national integration and cohesion that discourages marginalization of students from low Socio-Economic Status. The results of the study stress measures to be taken by the policymakers for the formulation of admission tests that equally correspond to ensuring equal competition opportunities for students with varying socio-economic and educational systems backgrounds.